Experimental study of the behaviors of stabilized soil confined by polyvinyl chloride pipe. (10th December 2019) - Li, Shiyang; Huang, Xin; Wu, Shuaishuai; Zhang, Wuman
Highlights: The behaviors of confined stabilize soil under compressive loading are studied. A transition point is defined and a transition point model is developed. An ultimate condition model is proposed. Abstract: The resource utilization of the foundation soil in corrosive environments could be achieved effectively by the foundation treatment method of confined stabilized soil (CSS), which used polyvinyl chloride pipe to confine stabilized soil. The binder consisted of the expansive component (EC) and the cementing component. This paper studied the behaviors of CSS cylinders considering the experimental variables of mass ratio of EC and cementing component (0–1.00), binder content in soil (10–25%), water content in soil (17–32%), and confinement stiffness (0.17–0.52 GPa). The pretension of confinement pipe, stress-strain curve, failure mode, strength enhancement ratio, normalized stress-strain curve, and Poisson's ratio were analyzed. To evaluate the enhancement of EC, the transition point was defined as the point where Poisson's ratio of CSS became stable, and a transition point model was proposed. An ultimate condition model was further developed and the model performance was evaluated. Results show that the pretension of confinement pipe was formed effectively by EC during curing, the stress-strain curves were significantly bilinear until the ultimate strength was reached, and the ultimate strength and the corresponding axial strain of CSS were 1.66–5.57 and 6.47–32.63 times the unconfined ones, respectively. When the confinement stiffness kept the constant value, the strength enhancement ratio, the confinement efficiency and the stabilized value of Poisson's ratio of CSS were all affected mainly by the strength of USS. When the confinement stiffness varied, the behaviors became affected mainly by the confinement stiffness. The proposed models captured the experimental data with satisfactory accuracy.